Introduction to the GaLA Conf 2018 Special Issue - Pedro A. Santos; Remco Veltkamp; Joao Dias (Serious Games Society, 2018)
Introduction to the IJSG Special Issue dedicated to the best papers of Games and Learning Alliance Conference (GaLA Conf) 2017, Lisbon